Pengaruh Sosial Ekonomi, Demografi dan Kesehatan Mental Terhadap Status Putus Sekolah Pada Usia SMA di Sumatera Utara Tahun 2021 - Prido Putra Sinaga; Jeffry Raja Hamonangan Sitorus (Seminar Nasional Official Statistics, 2022)
Failing ini Education or dropping out of school can cause other social problems such as unemployment, crime and others. School dropouts still occurs in Indonesia, including North Sumatra which supports the 12-year compulsory education program. The average length of schooling in North Sumatra still hasn't reach the target and School Dropout Rate (APTS) is also above the national rate. This study aims to examine the factors that influence the school dropouts of 16-18 aged childrens in North Sumatra in 2021. Analytical method used is binary logistic regression analysis. It was found that the factors influencing the school dropouts in North Sumatra 2021 are the children’s working status, completeness of parents, poverty status, sex of children, birth order and behavioral or emotional disorders. Variables that have greater influence than others are children's working status and behavioral or emotional disorders. To overcome school dropout in North Sumatra It is advisable to pay more attention to these two variabes.